The arts of editing Medieval Greek and Latin a casebook - Göransson, Elisabet; Iversen, Gunilla 1941-; Crostini, Barbara; Jensen, Brian Møller 1948-; Kihlman, Erika; Odelman, Eva 1943-; Searby, Denis Michael 1963-; Pontifical Institute of Mediaeval Studies (Studies and texts, 2016)
"The Arts of Editing Medieval Greek and Latin: A Casebook is a collection of 18 case studies aimed at giving readers a chance to follow textual scholars as they tackle the kind of editorial challenges not normally discussed in manuals on textual criticism. The authors delve into methodological issues that include producing single-manuscript editions or those involving huge numbers of witnesses, editing different versions of the same author's text or anthologies of different authors, capturing stages of textual genesis, dealing with textual variability, relating text and image, utilizing digital tools, and more. They outline the challenges in the given editorial situation and explain the methodologies adopted in the editing process. The case studies are compared and contrasted in a concluding chapter that offers reflections on the editor's role and strategies. Without being prescriptive in the style of handbooks on textual philology, this book offers specific examples of the use to which the various tools in the editor's toolbag may be put in confronting unique editorial situations."--